Climate change and primary health care in Chakama, Kilifi County, Kenya - Muhsin Sheriff; Robert Mash (AOSIS, 2022)
Chakama is an area of 46 small villages in Kilifi County, Kenya. Climate change has led to more frequent and longer periods of drought in this semi-arid region as well as locust invasions. This has led to a lack of water, with many rivers drying up and poor water quality as a result of pollution of the remaining river water. The lack of water and locust invasion have led to a failure of the crops and loss of livestock. Many pastoralists and farmers have lost their livelihood. Wild animals from local nature reserves have also come into conflict with the community over water scarcity. Many families have migrated in search of water and income. The health effects are seen in the rising number of people suffering from malnutrition and gastroenteritis as well as in terms of mental health problems. Primary health care services are not always available, and the quality of such services is poor. Facilities and healthcare workers also struggle to be resilient in the face of the same environmental challenges. Local nongovernment organisations are attempting to assist through health and social services, community engagement and multisectoral action.